2018
DOI: 10.1017/jog.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Active seismic studies in valley glacier settings: strategies and limitations

Abstract: Subglacial tills play an important role in glacier dynamics but are difficult to characterize in situ. Amplitude Variation with Angle (AVA) analysis of seismic reflection data can distinguish between stiff tills and deformable tills. However, AVA analysis in mountain glacier environments can be problematic: reflections can be obscured by Rayleigh wave energy scattered from crevasses, and complex basal topography can impede the location of reflection points in 2-D acquisitions. We use a forward model to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Upstream of the grounding zone two retrieved estimates exhibit properties similar to those of water (kilometer 0-0.5); however, neither are unambiguous. values typical of those observed in dewatered tills ( Figure 6-7, Table 4) (Zechmann et al, 2018). Our estimates of V p and ρ for all lines are close to those estimated by Luthra et al (2016) in their active source seismic study of a major sticky spot beneath Whillans Ice Plain.…”
Section: Reflection Coefficients and Basal Propertiessupporting
confidence: 84%
See 2 more Smart Citations
“…Upstream of the grounding zone two retrieved estimates exhibit properties similar to those of water (kilometer 0-0.5); however, neither are unambiguous. values typical of those observed in dewatered tills ( Figure 6-7, Table 4) (Zechmann et al, 2018). Our estimates of V p and ρ for all lines are close to those estimated by Luthra et al (2016) in their active source seismic study of a major sticky spot beneath Whillans Ice Plain.…”
Section: Reflection Coefficients and Basal Propertiessupporting
confidence: 84%
“…Source size (A 0 ) is often estimated using the ratio of the primary bed return amplitude (A i ) and the long path multiple amplitude (A m,i ) (e.g. Röthlisberger, 1972;Smith, 1997;Peters et al, 2008;Brisbourne et al, 2017;Zechmann et al, 2018), as this approach can remove the need for an independent estimate of attenuation. However, low impedance contrast at the bed, low signal to noise ratios, or closely spaced subglacial reflectors, can all complicate the amplitude ratio method of determining source amplitude.…”
Section: Source Size and Attenuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shot or geophone coupling corrections were not performed as previous studies found this correction to be insensitive to the calculated reflectivity (Zechmann and others, 2018). Additionally, we anticipated this variation to be relatively small in comparison to the large range of first order multiple amplitude values and p-wave attenuation parameters used in Eqn (1).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…To further investigate the basal properties beneath Whillans Ice Stream's grounding zone, we here revisit the active-source seismic data reported by Horgan et al (2013b) and apply and extend amplitude analysis methods previously used in studies addressing the basal boundary of glaciers and ice sheets (e.g. Anandakrishnan, 2003b;Smith, 2007;Holland and Anandakrishnan, 2009;Brisbourne et al, 2017;Zechmann et al, 2018;Muto et al, 2019). These methods require source amplitude and path effects to be estimated, which is often challenging due to variability in source and receiver coupling and strong vertical gradients in density and seismic velocity in the firn.…”
Section: Introductionmentioning
confidence: 99%